Functional Plant Types Drive Plant Interactions in a Mediterranean Mountain Range - Macek, Petr; Prieto, Iván; Macková, Jana; Pistón, Nuria; Pugnaire, Francisco I. (Frontiers in Plant Science, 2016)
Shrubs have both positive (facilitation) and negative (competition) effects on understory plants, the net interaction effect being modulated by abiotic conditions. Overall shrubs influence to great extent the structure of plant communities where they have significant presence. Interactions in a plant community are quite diverse but little is known about their variability and effects at community level. Here we checked the effects of co-occurring shrub species from different functional groups on a focal understory species, determining mechanisms driving interaction outcome, and tested whether effects measured on the focal species were a proxy for effects measured at the community level. Growth, physiological, and reproductive traits of Euphorbia nicaeensis, our focal species, were recorded on individuals growing in association with four dominant shrub species and in adjacent open areas. We also recorded community composition and environmental conditions in each microhabitat. Shrubs provided environmental conditions for plant growth, which contrasted with open areas, including moister soil, greater N content, higher air temperatures, and lower radiation. Shrub-associated individuals showed lower reproductive effort and greater allocation to growth, while most physiological traits remained unaffected. Euphorbia individuals were bigger and had more leaf N under N-fixing than under non-fixing species. Soil moisture was also higher under N-fixing shrubs; therefore soil conditions in the understory may counter reduced light conditions. There was a significant effect of species identity and functional types in the outcome of plant interactions with consistent effects at individual and community levels. The contrasting allocation strategies to reproduction and growth in Euphorbia plants, either associated or not with shrubs, showed high phenotypic plasticity and evidence its ability to cope with contrasting environmental conditions.